GROWTH AND RESULTS Asystasia gangetica (L.) subsp. Micrantha FERTILIZED BIOURIN WITH DIFFERENT DOSAGE ON SOIL ADDED LIME - S. D., Pramuji; Kusumawati, N.N. C.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2024)
This research aims to determine plant growth and yield Asystasia gangetica (L.) subsp. Micrantha fertilized with biourin on soil with added lime and to find out the best dose of biourin fertilizer to increase growth and yield Asystasia gangetica (L.) subsp. Micrantha. This research was carried out at the Greenhouse Jl. Raya Sading No. 93 Mengwi, Badung, which lasted 15 weeks from preparation to slaughter, using a completely randomized design (CRD) with five treatments and six replications. The five treatment doses of biourine fertilizer are dose 0 l ha ?1 (D0), 2.500 l ha ?1 (D1), 5,000 l ha ?1 (D2), 7,500 l ha ?1 (D3), 10,000 l ha ?1 (D4). The variables observed are growth variables, yield variables and plant growth characteristic variables. The results showed that by administering a biourin dose of 2,500 l ha ?1 (5 m?/pot) (D1) in soil with added lime provides the best response to plant growth and yield Asystasia gangetica (L.) subsp. Micrantha